Bioaccumulation of cadmium and quantitative characterization of proteins ofSaccharomyces cerevisiae - Kumari, Sarla; Mohan, Chandra; Kumar, Vinod (International Journal of Psychosocial Rehabilitation, 2020)
Bioaccumulation using microbes is an efficient strategy for heavy metal removal due to its low cost, high efficiency, and ecofriendly nature. Recent inventions have been made to understand metal-microbe interaction and their application for metal accumulation. Yeast, being a typical eukaryote, has many essential features similar to those of higher eukaryotes and can be used to investigate various aspects of their cell biology. Saccharomyces cerevisiae can be used as a model system because of easy cultivation using normal media. It is therefore planned to investigate the bioaccumulation of cadmium by S. cerevisiae. Molecules that participate in the binding of metal ions have been identified and found in several species of yeast and other fungi. Proteins are able to transport a charged heavy metal ion across biological membranes. Metallothioneins, like proteins, are important mediators that help in metal uptake and hence accumulation, especially for cadmium. This paper attempts to present the correlation between cadmium concentrations in the environment and accumulation by S. cerevisiae, along with the involvement of metal-binding proteins.